دور الشركات السياحية في تسويق الخدمات الفندقية دراسة تطبيقية على فندق التوفيق بلازا (Comprehensive Journal of Science, 2025)
Tourism companies are best placed to market tourism services, so this aspect warrants study and analysis. The researcher studied this topic, namely the role of tourism companies in marketing hotel services. The research aimed to find a solution to the problem of hotel management's failure to engage with tourism companies in marketing services. To obtain more accurate information, the researcher relied on a questionnaire form, which was randomly distributed to a sample of (53) employees at Al Tawfiq Plaza Hotel. The percentage method was used. It is worth noting that the researcher sought to prove the hypothesis that there is a statistically significant relationship between tourism companies and the marketing of hotel services. To achieve the research objectives, the researcher applied the descriptive and analytical approach. The research reached several results, including: the hotel's engagement with tourism companies increases sales, in addition to the hotel granting companies financial and moral discounts. At the same time, the researcher also works to use the criteria method for selecting tourism companies. The researcher believes that the hotel should take into account the opinions of tourism companies in the process of marketing hotel services. Hotel management must also work according to the requirements of tourism companies for successful marketing. Hotel management must focus on an effective system for motivating and encouraging tourism companies, whether financial or indirect. Keywords: hotel services, tourism com.